US maize data reveals adaptation to heat and water stress - Thomas, Timothy S. (International Food Policy Research Institute, 2015)
Heat is a serious barrier to maize productivity increases, and heat is expected to rise as a result of climate change. Using county-level annual yields for rainfed maize for 2,616 US counties from 1980 to 2010, we conduct a multivariate, nonparametric yield response analysis to weather, maize price, and time trend to project climate impact on maize and to compare with climate projections from crop models. When we compare with climate impacts predicted by biophysical models, we find that our analysis tends to support the most pessimistic of the biophysical model projections for climate change. We also demonstrate that growth in maize yields in the United States between 1980 and 2010 was higher under high temperatures than under moderate temperatures, with yields growing 20.2 percent faster when the mean daily maximum temperature for the warmest month ranged from 34 to 35 degrees Celsius instead of 28 to 29 degrees. Similarly, we find that US maize has become more tolerant of lower rainfall levels, with yields growing 15.9 percent faster between 1980 and 2010 when rainfall is below 250 millimeters in the first four months of the growing period compared with when it is between 400 and 450 millimeters (the optimal amount of rainfall). This suggests that significant adaptation to current and future effects of climate change is already taking place for US maize.